ANALYSIS OF THE INFLUENCE OF GOVERNMENT INVESTMENT, GROSS DOMESTIC PRODUCT, REAL INTEREST RATES, AND THE GOVERNMENT'S POLICY OF INVESTMENT TO PRIVATE INVESTMENT REALIZATION IN INDONESIA FROM 1972 TO 2005 - Haptari, Vissia Dewi (Polytechnic of State Finance STAN, 2016)
This study tests the joint effects of Government Investment, Gross Domestic Product (GDP), RealÂ Interest Rates, and Government's Policy on realization of private investment in Indonesia from 1972Â until 2005. Government investment, the level of GDP and real interest rate directly have causality relationship with private investment, meaning every change in government investment, the level of GDP and real interest rate will cause positive change to private investment. On the other hand, the level of real interest rate does not have significant effect on investment, meaning the level of interest rate is not theÂ only main cause, there are some other factors such as: inefficient institution condition which can be seen from complexity of rules, legal compliance system, and political stability.